A colloid electrolyte taking covalent organic framework nanosheet as dispersoid, and a preparation method and application thereof
Patent Information
- Application Number
- CN202310554689.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-16
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-05-16
AI Technical Summary
然而,现如今大多数的电解液改性策略都是自牺牲型的,即起作用的添加剂或者其他分子会在循环过程中被不断消耗,直至循环后期被彻底耗尽
[0034]1)本发明的方法简单,仅需对现有的商业化电解液进行改性,成本低廉及易于产业化;
Smart Images

Figure CN116598574B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion / lithium metal batteries, and specifically relates to a colloidal electrolyte using covalent organic frameworks (COFs) nanosheets as the dispersion medium, its preparation method, and its application. Background Technology
[0002] Battery technology has played a crucial role in addressing the global energy crisis, enabling the efficient utilization of renewable but unstable energy sources such as solar and wind power. With rapid social and economic development, the demand for high-energy-density energy storage systems has become increasingly urgent. Currently, the most commercially viable lithium-ion batteries, due to their relatively low theoretical energy density, can no longer meet the long-range requirements of applications such as electric vehicles and portable electronic devices. Developing battery systems with higher energy density has become an urgent societal need.
[0003] High-nickel layered cathode (LiNi) x Co y Mn 1-x-y The theoretical specific capacity of lithium metal batteries (O2, NCM, x≥0.5) is as high as 270 mAh / g. When paired with a lithium metal anode, it can significantly improve the battery's energy density, which is far higher than that of currently commercialized lithium-ion batteries (LIBs), making it one of the most promising next-generation energy storage systems. However, a series of problems during the charging and discharging process of lithium metal batteries based on high-nickel layered cathodes have also inhibited their commercial application: 1) Transition metal elements in the cathode dissolve in the electrolyte during charging and discharging, and shuttle through the separator to the surface of the anode, causing irreversible loss of active materials and seriously affecting the cycle stability of the battery; 2) The higher charging cut-off voltage of the battery can further improve the battery's energy density, but the high oxidation state of transition metal elements in the cathode can catalyze the decomposition of electrolyte solvent molecules; 3) Due to the low electrochemical redox potential of lithium metal (-3.04V vs. SHE), it can spontaneously undergo side reactions with electrolyte solvent molecules, and the slow desolvation kinetics of lithium ions further exacerbate these side reactions. Currently, to address the aforementioned issues, researchers have proposed strategies such as electrolyte additives, high-concentration electrolytes, and locally high-concentration electrolytes. However, most current electrolyte modification strategies are self-sacrificing, meaning that the effective additives or other molecules are continuously consumed during cycling until they are completely depleted in the later stages of cycling. Therefore, developing a non-self-sacrificing, stable electrolyte system that can simultaneously suppress the dissolution of transition metals from layered cathodes and side reactions at the electrode / electrolyte interface would significantly advance the future commercialization of lithium metal batteries based on high-nickel layered cathodes. Summary of the Invention
[0004] To overcome the shortcomings and deficiencies of the prior art, the primary objective of this invention is to provide a colloidal electrolyte using covalent organic frameworks (COFs) nanosheets as the dispersion phase. In the colloidal electrolyte provided by this invention, the COFs nanosheets, acting as the dispersion phase, can utilize their polar functional groups to co-adsorb lithium ions and lithium salt anions, promoting the formation of more inorganic solid electrolyte interfacial phases on the surfaces of the positive and negative electrodes. The electrode interface rich in inorganic solid electrolyte interfacial phases suppresses the decomposition of solvent molecules and the dissolution of transition metals on the surface of the high-nickel layered positive electrode, while also inhibiting side reactions between solvent molecules and lithium metal.
[0005] Another objective of this invention is to provide a method for preparing the above-mentioned colloidal electrolyte using covalent organic framework (COF) nanosheets as the dispersion medium. This method first synthesizes the covalent organic framework material as the dispersion medium of the colloidal electrolyte via a room-temperature solution synthesis method. This method is applicable to all COFs synthesized using aldehyde and amino monomers as raw materials, and the COFs synthesized by this method have lateral and longitudinal dimensions of less than 100 nm, making them ideal materials for use as the dispersion medium of colloidal electrolytes. Then, using the above-synthesized covalent organic framework material as the dispersion medium, the covalent organic framework material is dispersed in a commercial electrolyte to obtain a colloidal electrolyte using the covalent organic framework material as the dispersion medium.
[0006] Another objective of this invention is to provide the application of the above-mentioned colloidal electrolyte with covalent organic frameworks (COFs) nanosheets as the dispersion medium in lithium metal batteries.
[0007] The objective of this invention is achieved through the following solution:
[0008] A colloidal electrolyte using covalent organic frameworks (COFs) nanosheets as the dispersion medium includes covalent organic framework materials and a basic electrolyte.
[0009] The base electrolyte is a lithium-ion battery electrolyte, preferably one of commercial ester electrolytes and ether electrolytes, more preferably 1.2M LiPF6 EC:EMC (w / w 3:7).
[0010] The covalent organic framework material is a COF synthesized using aldehyde monomers and amino monomers as raw materials.
[0011] The covalent organic framework material described above can have its monomer structure designed according to its functionalization effect on the electrolyte. In this paper, the structure shown in Formula I is preferred:
[0012]
[0013] The amounts of the covalent organic framework material and the basic electrolyte are such that the concentration of the covalent organic framework material in the basic electrolyte is 0.1–10 g / L.
[0014] A method for preparing the above-mentioned colloidal electrolyte with a covalent organic framework as the dispersion phase includes the following steps:
[0015] (1) Preparation of COFs materials: Aldehyde monomers, amino monomers and solvents are mixed and stirred evenly, and then scandium trifluoromethanesulfonate solution is added to obtain a mixed solution. Argon gas is introduced and the mixture is sealed and stirred at room temperature. After the reaction is completed, COFs materials are obtained.
[0016] (2) Preparation of COFs colloidal electrolyte: The prepared COFs material is transferred to a glove box and the COFs material is uniformly dispersed in the base electrolyte to obtain COFs colloidal electrolyte, which is a colloidal electrolyte with covalent organic framework as the dispersion phase.
[0017] The aldehyde monomer mentioned in step (1) is trialdehyde phloroglucinol (Tp), and the amino monomer is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (Tta), with the specific structures shown below:
[0018]
[0019] The reaction molar ratio of the aldehyde monomer to the amino monomer in step (1) is 1:1.
[0020] The solvent used in step (1) is preferably dichloromethane and acetonitrile, with a volume ratio of dichloromethane to acetonitrile of 1:10 to 45, preferably 1:27.
[0021] In step (1), the preferred ratio of aldehyde monomer to dichloromethane is 99.6 mg: 4 to 12 ml, and more preferably 99.6 mg: 8 ml.
[0022] In step (1), the aldehyde monomer, amino monomer, and solvent are mixed and stirred evenly. Preferably, the aldehyde monomer and dichloromethane are mixed first, ultrasonically dispersed evenly, then acetonitrile is added, stirred at room temperature, and then the amino monomer is added, stirred to dissolve and mix evenly. The ultrasonic time after mixing the aldehyde monomer and dichloromethane is preferably 10-50 s.
[0023] The concentration of the scandium trifluoromethanesulfonate solution in step (1) is 2.5 to 4.5 g / L, preferably 3.5 g / L.
[0024] The amount of scandium trifluoromethanesulfonate solution used in step (1) satisfies the following condition: the molar ratio of amino group to scandium trifluoromethanesulfonate in the amino monomer is 12.5:1.
[0025] After argon gas is introduced in step (1), the reaction time of the mixed solution is 10 to 30 hours. Stirring is only to ensure sufficient contact between the raw materials, so there is no need to limit the stirring speed.
[0026] After the reaction in step (1) is completed, the following purification steps are also included: NaCl aqueous solution is added to the reaction product to precipitate the prepared COFs nanosheets. After precipitation, the nanosheets are washed with acetone, N,N-dimethylformamide, and chloroform, respectively, and then dried to obtain the COFs material. The amount of NaCl used is such that 0.5–3.3 mmol of NaCl is added for every 99.6 mg of aldehyde monomer, and the concentration of the NaCl aqueous solution is 0.5–1.5 mol / L. The drying conditions after washing are vacuum 60–80℃ and drying time is 8–12 h. The COFs powder obtained after drying is named TpTta.
[0027] Before transferring the prepared COFs material to the glove box in step (2), it is preferable to first place it in a high-speed planetary ball mill for ball milling until the transverse dimension of TpTta is below 100 nm, wherein the ball milling speed is 1000-2000 r / min and the ball milling time is 2-12 h; after ball milling, the obtained COFs powder is dried again to remove the water adsorbed during the drying process, wherein the drying conditions are vacuum drying at 60-80℃ for 8-12 h.
[0028] The concentration of COFs material dispersed in the basic electrolyte in step (2) is 0.1 to 10 g / L.
[0029] The uniform dispersion mentioned in step (2) refers to dispersion by stirring and / or ultrasound, preferably by stirring the mixed solution for 1 to 3 hours and then ultrasound for 2 to 6 hours.
[0030] The colloidal electrolyte obtained in step (2) is named TpTta colloidal electrolyte (abbreviated as TpTta CE).
[0031] The above-mentioned colloidal electrolytes with covalent organic frameworks as the dispersion medium are used in lithium metal batteries.
[0032] The lithium metal battery mentioned is a lithium metal battery based on a high-nickel layered cathode.
[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0034] 1) The method of the present invention is simple, requiring only modification of existing commercial electrolytes, and is low in cost and easy to industrialize;
[0035] 2) This invention uses covalent organic framework materials as the dispersion medium of colloidal electrolytes. The prepared covalent organic framework materials have the characteristics of porous structure and high specific surface area, which is beneficial to reduce the amount of COFs dispersion medium used.
[0036] 3) The COFs colloidal electrolyte (TpTta CE) of the present invention can change the solvation structure of lithium ions through the co-adsorption of lithium ions and anions by TpTta, and promote the formation of more inorganic solid electrolyte interface phases on the electrode surface. This phase can inhibit the decomposition of solvent molecules on the electrode surface and inhibit the precipitation of positive electrode transition metal ions.
[0037] 4) The colloidal electrolyte of this invention can be directly used as an electrolyte in lithium metal batteries based on high-nickel layered cathodes. TpTta does not undergo side reactions during battery cycling, which differs from previously reported self-sacrificing strategies. The colloidal electrolyte can effectively maintain the cycling stability of lithium metal batteries for a long time, with a volume retention of 78.2%–80.5% after 150 cycles. Lithium metal batteries assembled with the colloidal electrolyte (TpTta CE) exhibit good cycling stability at high charging cutoff voltages. Furthermore, this electrolyte is characterized by rapid preparation and low cost, showing excellent prospects for large-scale production. Attached Figure Description
[0038] Figure 1 The infrared spectrum of TpTta prepared in Example 1;
[0039] Figure 2 A photograph of the colloidal electrolyte obtained in Example 1;
[0040] Figure 3 Cyclic test results of a lithium metal battery assembled with the colloidal electrolyte prepared in Example 1;
[0041] Figure 4 Cyclic test results of a lithium metal battery assembled with the colloidal electrolyte prepared in Example 2;
[0042] Figure 5 Cyclic test results of a lithium metal battery assembled with the colloidal electrolyte prepared in Example 3. Detailed Implementation
[0043] The present invention will be further described in detail below with reference to embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0044] In the examples, the high-nickel layered cathode (LiNi) 0.8Co 0.1 Mn 0.1 O2 can be purchased from Ningbo Ronbay New Energy Technology Co., Ltd.
[0045] Example 1
[0046] (1) Preparation of TpTta: A mixture of 99.6 mg of trialdehyde phloroglucinol and 8 mL of dichloromethane was added to a round-bottom flask and ultrasonically dispersed for 10 s. 216 mL of acetonitrile was added to the round-bottom flask and ultrasonicated at room temperature for 1 min. Then, 168 mg of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine was added and stirred to dissolve, yielding a mixed solution. A scandium trifluoromethanesulfonate acetonitrile solution with a concentration of 3.5 g / L was prepared and added to the mixed solution prepared above. The molar ratio of amino group to scandium trifluoromethanesulfonate in the amino monomer was 12.5. After purging with argon gas, the mixture was sealed and stirred at room temperature for 10 h. After the reaction was completed, 0.5 mmol of NaCl was slowly added to a test tube to precipitate the prepared TpTta nanosheets. After sedimentation, the TpTta nanosheets were washed with acetone, N,N-dimethylformamide and chloroform, respectively. After washing, they were dried under vacuum at 60°C for 8 hours to obtain TpTta powder.
[0047] (2) Preparation of TpTta colloidal electrolyte: The prepared TpTta powder was ball-milled in a high-speed planetary ball mill at a speed of 1000 r / min for 2 h. After ball milling, the obtained COFs powder was dried again under vacuum at 60 °C for 8 h. The TpTta powder was transferred to an argon-atmosphere glove box. The concentration of TpTta dispersed in a commercial ester electrolyte (1.2 M LiPF6EC:EMC (w / w 3:7)) was 0.1 g / L. After dispersion, the colloidal electrolyte was stirred for 1 h and sonicated for 2 h. The resulting electrolyte was the TpTta colloidal electrolyte.
[0048] (3) Assemble the colloidal electrolyte obtained in step (2) into a high-nickel layered cathode (LiNi) 0.8 Co 0.1 Mn 0.1 Lithium metal batteries (O2).
[0049] The structure of TpTta prepared in this embodiment is shown in Formula I. The carbonyl and triazine groups in this structure can adsorb lithium ions, and the secondary amine group can adsorb lithium salt anions. Figure 1 The infrared spectrum of TpTta prepared in this embodiment. Figure 2 The image shows a photograph of the electrolyte obtained in this embodiment. It can be seen from the image that the electrolyte exhibits a significant Tyndall effect and is classified as a colloidal electrolyte. Figure 3This is a cycle test diagram of a lithium metal battery assembled with the colloidal electrolyte prepared in this example. From... Figure 3 As can be seen, lithium metal batteries using gel electrolytes can still maintain good cycle stability at a current density of C / 3 and a charging cutoff voltage of 4.7V, with a volume retention rate of 78.2% after 150 cycles. Figure 3 The BE in this example is a commercially available ester electrolyte without TpTta, and its capacity retention after 150 cycles is only 72.7%. Compared to an unmodified commercial ester electrolyte (1.2M LiPF6 EC:EMC (w / w 3:7)), the colloidal electrolyte prepared in this example exhibits better cycling stability, indicating that the TpTta CE colloidal electrolyte has a significant effect on suppressing the dissolution of transition metals in the cathode and side reactions at the electrode / electrolyte interface.
[0050] Example 2
[0051] (1) Preparation of TpTta: A mixture of 99.6 mg of trialdehyde phloroglucinol and 8 mL of dichloromethane was added to a round-bottom flask and ultrasonically dispersed for 30 s. 216 mL of acetonitrile was added to the round-bottom flask and ultrasonicated at room temperature for 3 min. Then, 168 mg of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine was added and stirred to dissolve. A scandium trifluoromethanesulfonate solution with a concentration of 3.5 g / L was prepared and added to the above-prepared mixed solution. The molar ratio of amino group to scandium trifluoromethanesulfonate in the amino monomer was 12.5. After purging with argon gas, the mixture was sealed and stirred at room temperature for 20 h. After the reaction was completed, 2 mmol of NaCl was slowly added to a test tube to precipitate the prepared TpTta nanosheets. After sedimentation, the TpTta nanosheets were washed with acetone, N,N-dimethylformamide and chloroform, respectively. After washing, they were dried in a vacuum at 70°C for 10 hours to obtain TpTta powder.
[0052] (2) Preparation of TpTta colloidal electrolyte: The prepared TpTta powder was ball-milled in a high-speed planetary ball mill at a speed of 1500 r / min for 7 h. After ball milling, the obtained COFs powder was dried again under vacuum at 70 °C for 10 h. The TpTta powder was transferred to an argon-atmosphere glove box. The concentration of TpTta dispersed in a commercial ester electrolyte (1.2 M LiPF6EC:EMC (w / w 3:7)) was 5 g / L. After dispersion, the colloidal electrolyte was stirred for 2 h and sonicated for 4 h. The resulting electrolyte was the TpTta colloidal electrolyte.
[0053] (3) Assemble the colloidal electrolyte obtained in step (2) into a high-nickel layered cathode (LiNi) 0.8 Co 0.1 Mn 0.1Lithium metal batteries (O2).
[0054] Figure 4 This is a cycle test diagram of a lithium metal battery assembled with the colloidal electrolyte prepared in this example. From... Figure 4 As can be seen, lithium metal batteries using colloidal electrolytes maintain good cycle stability at a current density of C / 3 and a charging cutoff voltage of 4.7V, with a volume retention of 80.5% after 150 cycles, significantly better than... Figure 3 Commercial ester electrolytes.
[0055] Example 3
[0056] (1) Preparation of TpTta: A mixture of 99.6 mg of trialdehyde phloroglucinol and 8 mL of dichloromethane was added to a round-bottom flask and ultrasonically dispersed for 50 s. 216 mL of acetonitrile was added to the round-bottom flask and ultrasonicated at room temperature for 5 min. Then, 168 mg of 2,4,6-tris(4-aminophenyl)-1,3,5-triazine was added and stirred to dissolve. An acetonitrile solution of scandium trifluoromethanesulfonate with a concentration of 3.5 g / L was prepared and added to the above-prepared mixed solution. The molar ratio of amino group to scandium trifluoromethanesulfonate in the amino monomer was 12.5. After purging with argon gas, the mixture was sealed and stirred at room temperature for 30 h. After the reaction was completed, 3.3 mmol of NaCl was slowly added to a test tube to precipitate the prepared TpTta nanosheets. After sedimentation, the TpTta nanosheets were washed with acetone, N,N-dimethylformamide and chloroform, respectively. After washing, they were dried in a vacuum at 80°C for 12 hours to obtain TpTta powder.
[0057] (2) Preparation of TpTta colloidal electrolyte: The prepared TpTta powder was ball-milled in a high-speed planetary ball mill at a speed of 2000 r / min for 12 h. After ball milling, the obtained COFs powder was dried again under vacuum at 80 °C for 12 h. The TpTta powder was transferred to an argon-atmosphere glove box. The concentration of TpTta dispersed in a commercial ester electrolyte (1.2 M LiPF6EC:EMC (w / w 3:7)) was 10 g / L. After dispersion, the colloidal electrolyte was stirred for 3 h and sonicated for 6 h. The resulting electrolyte was the TpTta colloidal electrolyte.
[0058] (3) Assemble the colloidal electrolyte obtained in step (2) into a high-nickel layered cathode (LiNi) 0.8 Co 0.1 Mn 0.1 Lithium metal batteries (O2).
[0059] Figure 5 This is a cycle test diagram of a lithium metal battery assembled with the colloidal electrolyte prepared in this example. From... Figure 5 As can be seen, lithium metal batteries using colloidal electrolytes maintain good cycle stability at a current density of C / 3 and a charging cutoff voltage of 4.7V, with a volume retention of 78.6% after 150 cycles, significantly better than... Figure 3 Commercial ester electrolytes.
[0060] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A colloidal electrolyte using covalent organic framework nanomaterials as the dispersion phase, characterized in that... Including covalent organic framework materials and basic electrolytes; The structure of the covalent organic framework material is shown in Equation I below: 。 2. The colloidal electrolyte using covalent organic framework nanomaterials as the dispersion phase according to claim 1, characterized in that: The basic electrolyte is a commercial lithium-ion battery electrolyte.
3. The colloidal electrolyte using covalent organic framework nanomaterials as the dispersion medium according to claim 1, characterized in that: The basic electrolyte is one of commercially available ester electrolytes and ether electrolytes.
4. The colloidal electrolyte using covalent organic framework nanomaterials as the dispersion phase according to any one of claims 1-3, characterized in that: The amounts of the covalent organic framework material and the basic electrolyte are such that the concentration of the covalent organic framework material in the basic electrolyte is 0.1~10 g / L.
5. A method for preparing a colloidal electrolyte using covalent organic framework nanomaterials as the dispersion phase according to any one of claims 1-4, characterized in that... Includes the following steps: (1) Preparation of COFs materials: The aldehyde monomer, amino monomer and solvent are mixed and stirred evenly, and then scandium trifluoromethanesulfonate solution is added to obtain a mixed solution. After argon gas is introduced, the mixture is sealed and stirred at room temperature. After the reaction is completed, COFs materials are obtained. (2) Preparation of colloidal electrolyte: The prepared COFs material is transferred to a glove box and the COFs material is uniformly dispersed in the base electrolyte to obtain the COFs colloidal electrolyte.
6. The method for preparing a colloidal electrolyte using covalent organic framework nanomaterials as the dispersion phase according to claim 5, characterized in that: The aldehyde monomer mentioned in step (1) is trialdehyde phloroglucinol, and the amino monomer is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine.
7. The method for preparing a colloidal electrolyte using covalent organic framework nanomaterials as the dispersion phase according to claim 5, characterized in that: The molar ratio of the aldehyde monomer to the amino monomer in step (1) is 1:1; The amount of scandium trifluoromethanesulfonate solution used in step (1) satisfies the following condition: the molar ratio of amino group to scandium trifluoromethanesulfonate in the amino monomer is 12.5:1; The reaction time of the mixed solution after argon gas is introduced in step (1) is 10~30h.
8. The application of the colloidal electrolyte with covalent organic framework nanomaterials as the dispersion medium according to any one of claims 1-4 in lithium metal batteries.
9. The application of the colloidal electrolyte with covalent organic framework nanomaterials as the dispersion phase according to claim 8 in lithium metal batteries, characterized in that: The lithium metal battery mentioned is a lithium metal battery based on a high-nickel layered cathode.
Citation Information
Patent Citations
Electrolyte for aluminum air battery and preparation method of electrolyte
CN113363628A
Mixed matrix membrane for gas separation and preparation method and application thereof
CN115970524A